Aerial imagination in Cuba - Boudreault-Fournier, Alexandrine, author.
1 online resource.
Keywords: Aerial Imagination in Cuba is a visual, ethnographic, sensorial, and poetic engagement with how Cubans imagine the sky as a medium that allows things to circulate. What do wi-fi antennas, cactuses, pigeons, lottery, and congas have in common? This book offers a series of illustrated ethno-fictional stories to explore various practices and beliefs that have seemingly nothing in common. But if you look at the sky, there is more than meets the eye. By discussing the natural, religious, and human-made visible and invisible aerial infrastructures--or systems of circulation--through short illustrated vignettes, Aerial Imagination in Cuba offers a highly creative way to explore the aerial space in Santiago de Cuba today.